2011
DOI: 10.1016/j.cellimm.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant ROCK activation promotes the development of type I diabetes in NOD mice

Abstract: Aberrant production of IL-21 by T cells is critical for the development of type 1 diabetes (T1D) in NOD mice. The pathogenic effects of IL-21 are partly due to its ability to promote the generation of TH-17 cells. Interferon Regulatory Factor (IRF4) is a crucial regulator of IL-17 and IL-21 production. We recently found that the serine-threonine kinase ROCK2 phosphorylates IRF4 and regulates its ability to control IL-17 and IL-21 production. Here we show that NOD T cells aberrantly activate ROCK2. We furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Targeted Rock inhibition could serve as a potential therapeutic approach for many debilitating diseases, including cancer ( Itoh et al, 1999 ; Kuzelová and Hrkal, 2008 ; Narumiya et al, 2009 ; Liu et al, 2011 ), obesity ( Hara et al, 2011 ; Washida et al, 2011 ; Tokuyama et al, 2012 ), diabetes ( Biswas et al, 2011 ), hypertension ( Connolly and Aaronson, 2011 ), atherosclerosis ( Zhou et al, 2011 ), and cardiovascular diseases ( Dong et al, 2010 ). However, the Rock-Myosin II pathway is central to numerous cellular processes and signaling networks ( Wei et al, 2001 ; Thumkeo et al, 2003 ; Shimizu et al, 2005 ; Thumkeo et al, 2005 ; Kamijo et al, 2011 ), suggesting that global inhibition of Rock function would likely disrupt multiple cellular processes with detrimental side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted Rock inhibition could serve as a potential therapeutic approach for many debilitating diseases, including cancer ( Itoh et al, 1999 ; Kuzelová and Hrkal, 2008 ; Narumiya et al, 2009 ; Liu et al, 2011 ), obesity ( Hara et al, 2011 ; Washida et al, 2011 ; Tokuyama et al, 2012 ), diabetes ( Biswas et al, 2011 ), hypertension ( Connolly and Aaronson, 2011 ), atherosclerosis ( Zhou et al, 2011 ), and cardiovascular diseases ( Dong et al, 2010 ). However, the Rock-Myosin II pathway is central to numerous cellular processes and signaling networks ( Wei et al, 2001 ; Thumkeo et al, 2003 ; Shimizu et al, 2005 ; Thumkeo et al, 2005 ; Kamijo et al, 2011 ), suggesting that global inhibition of Rock function would likely disrupt multiple cellular processes with detrimental side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and cell-based approaches demonstrated that the Rock–myosin II pathway is used to control the cell behaviors that facilitate tissue morphogenesis in animals. As a result, targeted Rock inhibition is viewed as a viable therapeutic approach for treating many clinical conditions, including cancer ( Liu et al , 2011 ), obesity ( Hara et al , 2011 ), type I diabetes ( Biswas et al , 2011 ), pulmonary hypertension ( Connolly and Aaronson, 2011 ), and many others (reviewed in Dong et al , 2011 ). The central role of Rock also makes global inhibition of Rock a challenge due to possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to NK cells, NKT cell development can be sustained by IL-15Rα expressed on non-hematopoietic cells [36,37]. Similarly, IFN-γ production by NKT cells following α-galactosylceramide stimulation is deficient in Il15ra −/− mice suggesting that IL-15 signalling also regulates their activation [33,37]. In contrast to NK cells, IL-15 mediated survival of NKT cells is not mediated primarily through the upregulation of anti-apoptotic factors [30].…”
Section: Resultsmentioning
confidence: 99%